2003
DOI: 10.1086/367619
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Emission from Multiphase Shock in the Large Magellanic Cloud Supernova Remnant N49

Abstract: The supernova remnant (SNR) N49 in the Large Magellanic Cloud has been observed with the Advanced CCD Imaging Spectrometer (ACIS) on board the Chandra X-Ray Observatory. The superb angular resolution of the Chandra/ACIS images resolves a point source, the likely X-ray counterpart of soft gammaray repeater SGR 0526À66, and the diffuse filaments and knots across the SNR. These filamentary features represent the blast wave sweeping through the ambient interstellar medium and nearby dense molecular clouds. We dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 54 publications
12
77
1
Order By: Relevance
“…Based on a simple Sedov model for the SNR, Hughes et al (1998) concluded that the swept-up mass was the order of 200 M . Park et al (2003) recently conducted a detailed study of its X-ray properties using Chandra, confirming that the SNR is relatively young, on the order of 6000 yrs. They find that although most of the emission is dominated by interstellar material (ISM), the Chandra observations appear to show "explosion fragments" on the SW side of the SNR in X-rays.…”
Section: Introductionmentioning
confidence: 92%
“…Based on a simple Sedov model for the SNR, Hughes et al (1998) concluded that the swept-up mass was the order of 200 M . Park et al (2003) recently conducted a detailed study of its X-ray properties using Chandra, confirming that the SNR is relatively young, on the order of 6000 yrs. They find that although most of the emission is dominated by interstellar material (ISM), the Chandra observations appear to show "explosion fragments" on the SW side of the SNR in X-rays.…”
Section: Introductionmentioning
confidence: 92%
“…No compelling evidence for overabundant O or Fe is found, but Si-and S-rich ejecta features are detected by Chandra (Park et al 2003a(Park et al , 2012. These can be interpreted as explosive O-burning or incomplete Si-burning deep inside a CC SN explosion; however, the Si/S ejecta mass ratio favour a type Ia origin (Park et al 2003a(Park et al , 2012. The soft gamma-ray repeater SGR…”
Section: Appendix A: the Epic Backgroundmentioning
confidence: 99%
“…To investigate the spatial distribution of Si and S line emission across the remnant on a finer scale than that of the spectral extraction regions, we produced continuum-subtracted (CS) line images and equivalent-width ( EW ) images (see, e.g., Park et al 2003), shown in Figure 5. Narrowband images used for deriving the CS and EW images were filtered in energy according to Table 4 and binned by 8 00 to provide a sufficient number of counts in the faint SNR regions.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Another example is the only ME SNR in the Large Magellanic Cloud, N49 ( Brogan et al 2004). This remnant also has an irregular shell morphology in both radio and X-rays, with a bright region to the southeast (e.g., Park et al 2003), which can similarly be explained as resulting from expansion in a density gradient produced by the presence of a molecular cloud, as mapped by Banas et al (1997). Thus, if ME and MM SNRs are the same class of the SNRs and there is a single mechanism to explain their appearance and spectral characteristics, the observations of G349.7+ 0.2 would support the projection model.…”
Section: Implications For Mixed-morpholog Gy Snrsmentioning
confidence: 99%